Mathematical modelling and experimental study of carbonation of wollastonite in the aqueous media. (May 2019) - Yadav, Shashikant; Mehra, Anurag
Graphical abstract: Highlights: CO2 sequestration by carbonation of wollastonite in aqueous medium. Study the impact of incongruent dissolution on the carbonation of wollastonite. Mathematical model to predict the dissolution and precipitation of the mineral components. Abstract: Wollastonite (CaSiO3 ) is considered as one of the most suitable naturally occurring minerals for carbon dioxide (CO2 ) sequestration because of its high Calcium (Ca) content, which has an enormous potential to form stable carbonates. However, carbonation of CaSiO3 is a complex three–phase reaction involving CaSiO3, an aqueous solution, and gaseous CO2 . The reaction mechanism gets complicated further due to the formation of undissolved silica and product layers on the surface of CaSiO3 particles. The formation of these layers is caused by incongruent dissolution of CaSiO3 and precipitation of the carbonate occurring simultaneously. In this study, a mathematical model was developed to understand the mechanism of dissolution and precipitation of the mineral components. The model functioned under various temperatures, pressures, S/L ratios and particle size fractions. The model was then validated using experimental data obtained by conducting experiments on the carbonation of CaSiO3 . It utilized the experimental results to eventually calculate the Damkohler number ( Da ) to understand the rate controlling mechanism of the reaction.